Deinstitutionalization and people with intellectual disabilities : in and out of institutions - Johnson, Kelley, 1947-; Rannveig Traustadóttir, 1950- (Jessica Kingsley Publishers, 2005)
Deinstitutionalization and People with Intellectual Disabilities is an international collaboration between qualitative researchers and former institutional residents with intellectual disabilities that presents a comprehensive overview of personal and professional perspectives on deinstitutionalisation. Personal stories alternate with cultural and political analysis, and reflections on implementing and evaluating deinstitutionalisation. This great diversity of perspectives is complemented by insights into the personal and professional life of one institutional ex-resident, Thomas Allen, whose.